Media students' attitudes towards teaching informatics 1429 AH - 2008 AD (Journal of the College of Basic Education, 2023)
Information is considered an essential resource in any human activity, and an important element in the human relationship with his society, and the relationship of societies with each other through the basic aspects of life itself. People demand information that is appropriate, accurate, reliable, up-to-date, and available quickly and easily.The most important transformations that can be talked about and followed up on their stages in the media and communication revolution is the changes brought about by the information in the media institutions through the available media, including the written press that changes its work system. The entry of informatics into the editing rooms since the beginning of the eighties greatly affected the newspaper industry, journalistic writing methods, and the possibility of benefiting from the highways of information that are presented by the written press today to its readers in electronic newspapers on the Internet, which constitutes technical progress because multimedia technologies enable the journalist to attach graphics Pictures and data supplementing the text, as well as enabling the reader to obtain distinctive forms of the newspaper thanks to the possibility of selecting specific topics.